Cognitive context and syllogisms from ontologies for handling discrepancies in learning resources - Panayiotou, Christiana; Bennett, Brandon (My University, 2008)
The deployment of learning resources on the web by different experts has resulted in the accessibility of multiple viewpoints about the same topics. In this work we assume that learning resources are underpinned by ontologies. Different formalizations of domains may result from different contexts, different interpretation of terminology, different vocabularies to define concepts, incomplete knowledge and conflicting knowledge of the experts deriving the ontologies. We define the notion of cognitive learning context that refers to multiple and possibly inconsistent ontologies about a single topic. We then discuss how this notion relates to the cognitive states of ambiguity and inconsistency. Discrepancies in viewpoints can be identified via the inference of conflicting arguments from consistent subsets of statements. Two types of arguments are discussed, namely arguments inferred directly from taxonomic relations between concepts and arguments about the necessary and jointly sufficient features that define concepts.
Keywords: Semantics; Artificial intelligence; Bridge rules